INSERÇÃO PROFISSIONAL DE EGRESSOS DAS LICENCIATURAS INTERDISCIPLINARES: Trajetórias de Graduados em Ciências Humanas (UFMA- Campus Bacabal) - NASCIMENTO, Jéssica Rodrigues do (2023)
The present study is part of the research line “Educational Institutions, Curriculum, Training and Teaching Work” of the Graduate Program in Education at the Federal University of Maranhão – UFMA. With the theme: Professional insertion of Graduates of Interdisciplinary Degrees: Trajectories of Graduates in Human Sciences UFMA- Campus Bacabal. In this regard, the present study aims to analyze the professional insertion of graduates of the course through the study of academic and professional trajectories between 2014 and 2021. The question that guides the research is: The training offered through the interdisciplinary degree enables the insertion graduate professional in teaching for basic education?. To answer the question, the study adopts the historical-dialectical materialist theoretical perspective. The theoretical approach is based on authors who approach the theme, among which we highlight: Trottier (1998), Tanuri (2000), Saviani (2009), Nunes (2011), Rodriguez (2014) Carvalho (2016) and Libâneo (2016) ). The following methodological procedures were adopted: bibliographic and documental research based on the Pedagogical Project of the Course (PPC), Guidelines and Resolutions for the creation of the course; application of an on-line questionnaire and semi-structured interview, covering the three profiles of graduates, namely: 1) those who never started teaching; 2) those who abandoned the teaching career; 3) those who are acting as teachers; For data analysis, we will rely on Minayo (2000). Of the 124 graduates of the course between 2014 and 2021, 42 graduates participated in the survey by answering the on-line questionnaire, and 6 graduates were interviewed in order to delve into some questions. The survey revealed that 59.5% of the participants are women; 61.9% self identify as mixed race; 78.6% come from public schools; 73.8% are taking a lato sensu postgraduate course; 78.5% needed to work during graduation. When analyzing the data on the professional trajectory, we found that 52% of the graduates participating in the research are working as professors; 31% never started teaching and 17% abandoned the teaching career. The main conclusions of this study were the difficulties encountered for the professional insertion of these graduates, such as the precarious working conditions in public education and the lack of opportunity in job vacancies.